Asphydroxel: Asphalt Carbon Dioxide Capture by Synthesis of Potassium Hydroxide for Utilization of Palm Oil Bunch Ash Waste - rony sihombing (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2023)
Environmental pollution is the most common problem faced by Indonesia, for example, industrial waste. The country of Indonesia once occupied the first position in Southeast Asia, as a country with the worst air quality. In addition, Indonesia is the largest producer of crude palm oil (CPO) and palm oil plantations in the world. The industry produces the most solid waste in the form of empty palm oil bunches and requires a large area to store it. In order to reduce the storage area needed, empty palm oil bunches are burned to ashes or palm oil fuel ash (POFA). Therefore, we have the idea of absorbing CO2 gas and utilizing POFA as a mixture of concrete and asphalt, by converting it into a potassium chloride compound. Then, the electrolysis process is carried out to produce potassium hydroxide compounds. The potassium hydroxide compound will later be mixed with asphalt to produce Asphydroxel asphalt, which absorbs carbon dioxide. In implementing Asphydroxel, several parties are involved, such as oil palm smallholders, palm oil mills, asphalt company research teams, asphalt companies, and the government. It is predicte that this idea will prevent the buildup of bunch ash waste and air pollution which cause climate change